Small nucleolar RNA - Makarova, J. A.; Kramerov, D. A. (Molecular biology (New York), 2007)
The review considers small nucleolar RNAs (snoRNAs), an abundant group of non-protein-coding RNAs. In association with proteins, snoRNAs determine the two most common nucleotide modifications in rRNA and some other cell RNAs: 2'-O-methylation of ribose and pseudouridylation. In addition, snoRNAs are involved in pre-mRNA cleavage and the telomerase function. Almost all snoRNAs fall into two families, C/D and H/ACA, distinguished by conserved sequence boxes. Although the proteins of C/D and H/ACA snoRNPs have homologous regions, these snoRNPs are assembled differently. The RNA components of RNases P and MRP are also classed with snoRNAs. Another problem considered is the structure and function of small RNAs from Cajal bodies (small organelles associated with the nucleoli), which are similar to snoRNAs.